Computational analysis of air intake system for internal combustion engine in presence of acoustic resonator - Mohd Nasir, Kassim; Mahmoud Idres, Moumen Mohammed; Ahmad, Muhammad Iqbal; Rizman, Zairi Ismaiel (Asian Research Publishing Network (ARPN), 2015)
Volumetric efficiency is one of the important parameters which affect the performance of four-stroke engines. This study examines the effect of resonators on the volumetric efficiency over a wide range of engine speed. An intake system with and without resonator are simulated by using GT-POWER software. Intake systems with three configurations of resonators with various resonator volumes are represented in terms of volumetric efficiency. The three intake system configurations are in-series, side-branch and double resonator. The results obtained are compared with an intake system without resonator. An intake system with resonator gives a significant improvement of volumetric efficiency at medium and high speed compared to the intake system without resonator. Volumetric efficiency showed an increment when the volume of the resonator increased. Overall, simulations indicate that the presence of the resonator in the intake system affects the volumetric efficiency of the engine especially for single cylinder engines.